THE EFFECTIVENESS OF GROUP-BASED INTERVENTIONS IN ENHANCING SELF-COMPASSION: A SYSTEMATIC LITERATURE REVIEW - Wulantika, Wulantika (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Adolescence is a crucial developmental stage marked by rapid biological, psychological, and social changes that require adaptive coping and emotional regulation. Limited self-compassion during this period is often linked to self-criticism, anxiety, and challenges in achieving developmental tasks, potentially undermining mental well-being. This study conducted a systematic review to examine the effectiveness of group interventions in enhancing self-compassion, with emphasis on adolescents. Using a qualitative library research design guided by PRISMA, the review involved topic selection, database searches, screening through PICOS criteria, data extraction, and content analysis. Five relevant studies were identified, encompassing diverse group-based approaches such as Gestalt group counselling, Modified Mindful Self-Compassion (MMSC), gratitude-based group therapy, and online self-compassion psychotherapy. The findings consistently showed that group interventions improve self-compassion, which in turn fosters emotional regulation, self-acceptance, and psychological well-being. Programmes integrating mindfulness, spirituality, and digital delivery demonstrate adaptability across cultural and practical contexts. This review contributes to the field by synthesising evidence from varied intervention models and underscoring their relevance in educational and clinical settings. It highlights the value of accessible, structured group-based strategies to promote mental health in adolescents and other vulnerable populations. Future research with larger experimental designs is recommended to strengthen empirical validation and extend generalisability.